Do natural resources attract non-resource FDI? - Van der Ploeg, R; Poelhekke, S (University of Oxford, 2010)
A new and extensive panel of outward non-resource and resource FDI is used to investigate the effect of natural resources on the different components of FDI. Our main findings are as follows. First, for those countries which were not a resource producer before, a resource discovery causes non-resource FDI to fall by 16% in the short run and by 68% in the long run. Second, for those countries which were already a resource producer, a doubling of resource rents induces a 12.4% fall in non-resource FDI. Third, on average, the contraction in non-resource FDI outweighs the boom in resource FDI. Aggregate FDI falls by 4% if the resource bonanza is doubled. Finally, these negative effects on non-resource FDI are amplified through the positive spatial lags in non-resource FDI. We also find that resource FDI is vertical whereas non-resource FDI is of the export-fragmentation variety. Our main findings are robust to different measures of resource reserves and the oil price and to allowing for sample selection bias.